State funding of agricultural enterprises of Russia - I. V. Baranova; Yu. N. Denisenko; V. G. Lisitsyn (Зерновое хозяйство России, 2018)
At present, agriculture needs a strong state support. The state support is the source of financing for agriculture. The difference between agricultural production and the most sectors of the economy is that it is less efficient. The invested capital is less profitable. Therefore, agriculture is not able to compete equally with industry without external support, including state support. The article considers the main areas of funding for effective development of the agricultural sector. 9815 agricultural enterprises and organizations of the agro-industrial complex have used the State support due to the state program of the Rostov region. The federal budget gives subsidies for breed husbandry, basic seed-growing, fodder, purchase of mineral fertilizers, chemicals, etc. The largest share of federal budget expenditures to support the agro-industrial complex of the Rostov region consists of the funds for reimbursement of the interest rate on loans and loans granted to rural enterprises, which allows them to replenish working capital on time and to do the spring and harvesting work. The regional budget gives the subsides to support the programs of the AIC’s development, to form breed husbandry and basic seed-growing, to compensate the expenditures on the development of social infrastructure, to partially compensate electricity, mineral fertilizers and chemicals for plant protection, research and study of the AIC, reconstruction of reclamation systems, etc.